Pedagogical innovation: Facilitating knowledge development in a multi-layered, blended-learning environment - Parry, Z.; Baird, Craig; Pedigo, Kerry (Higher Education, teaching and learning, 2013)
This paper documents how a course originally designed to be delivered via traditional face-to-face methods and an additional distance-learning stream was redesigned to integrate both streams in a blended learning ‘classroom without walls’ virtual spaces environment. Discussed here are the formative feedback teaching elements and assessment methods utilised in the reshaped course, along with particular learning issues for transnational students. Addressed also for this new course model are the methods for moderating teaching and assessment practices to ensure fairness, equity, and compliance to university regulations. Tertiary learning and teaching is evolving through the use of innovative pedagogical practices utilizing social media, communication and information sharing technologies and virtual learning spaces. The use of online and blended learning approaches means that any student can be regarded as transnational in the sense they can learn in the culture and space of their choosing, at customized times to suit their lifestyle or availability. To support this choice, new courses must be constructed around learning flexibility in technology based virtual spaces; that is, classrooms without walls. In such settings, student centred learning can be facilitated through the use of technologies for engaging students in activities that have relevance to them, and encourage retention. Whatever the form of delivery, learning must involve reliable and equitable assessments to ensure that all students in virtual or classroom settings receive equal levels of formative feedback contextualised to the culture of learning found in their various international settings. This paper proposes that to cater for a mix of student learning styles, physical settings, and online technologies, a new multilayered approach to learning, called here ‘blended-blended’ learning can create success.